2009
DOI: 10.1155/2009/187615
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube‐Based Electrochemical Sensors: Principles  and  Applications  in  Biomedical  Systems

Abstract: Carbon nanotubes (CNTs) have received considerable attention in the field of electrochemical sensing, due to their unique structural, electronic and chemical properties, for instance, unique tubular nanostructure, large specific surface, excellent conductivity, modifiable sidewall, high conductivity, good biocompatibility, and so on. Here, we tried to give a comprehensive review on some important aspects of the applications of CNT-based electrochemical sensors in biomedical systems, including the electrochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(64 citation statements)
references
References 261 publications
0
63
0
1
Order By: Relevance
“…The peak current ratio Ipa/Ipc was 0.96, and the peak to peak separation, ΔEp = Epa − Epc, was 30 mV. The results indicated that CNTMEs are an excellent platform for constructing an electrochemical sensor for dyes bearing anthraquinone groups and improve the reversibility of the electron transfer process due to their electrocatalytic activities [29] toward these species, enhancing the current yielded and reducing peak-to-peak separations in comparison with the bare electrode. In order to improve the response of the CNTME, the same electrode was subjected to scans in acid medium in order to remove material from the organic solvent (DMF) on its surface, thus increasing its area.…”
Section: Voltammetric Behaviormentioning
confidence: 92%
See 2 more Smart Citations
“…The peak current ratio Ipa/Ipc was 0.96, and the peak to peak separation, ΔEp = Epa − Epc, was 30 mV. The results indicated that CNTMEs are an excellent platform for constructing an electrochemical sensor for dyes bearing anthraquinone groups and improve the reversibility of the electron transfer process due to their electrocatalytic activities [29] toward these species, enhancing the current yielded and reducing peak-to-peak separations in comparison with the bare electrode. In order to improve the response of the CNTME, the same electrode was subjected to scans in acid medium in order to remove material from the organic solvent (DMF) on its surface, thus increasing its area.…”
Section: Voltammetric Behaviormentioning
confidence: 92%
“…The great versatility of multiwalled carbon nanotubes as electrode modifiers has attracted attention [28][29][30][31][32][33][34][35][36]. They are fulfilling the growing demand for highly sensitive, reliable and inexpensive sensors for the measurement of hazardous compounds in environmental samples, usually in highly diluted forms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of the glucose oxidation peak indicates that the mildly alkaline conditions provided by the phosphate buffered saline is sufficient for the oxidation of glucose to gluconic acid catalyzed by the CNT-modified surface that also captures the resultant electron transfer efficiently. Though the exact mechanism for the electrocatalytic behavior of MWCNTs has not yet been deciphered, it is believed that a combination of defect sites at the cap and the presence of oxygen-containing functional groups contribute to the electrocatalytic effect of MWCNTs (Hu and Hu 2009). The alkaline medium has been reported to activate the surface functionalities in MWCNTs (Ye et al 2004).…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…They have unique characteristics such as high conductivity, nonvolatile nature, low toxicity, large electrochemical window, strong electrostatic field, and good electrochemical stability [4]. Because of special properties of RTILs, their applications are increasing in different fields [5] especially for improvement in enzyme electron transfer rate and stability [4,6,7].…”
Section: Introductionmentioning
confidence: 99%